Toksisitas Ekstrak N-heksan Daun Momordica charantia Terhadap Mortalitas Cacing Ascaris suum - Rosalind Angkawidjaja, Valerie; Adrianto, Hebert; Darmanto, Arief Gunawan (Indonesian Journal of Pharmaceutical Education, 2024)
The relatively high rate of helminth infections in Indonesia has prompted scientists to explore the potential of plants as natural anthelmintics, aiming to replace synthetic options that are known to have side effects. This study aims to determine the potential of n-hexane extract from Momordica charantia leaves to cause mortality in Ascaris suum. This research is an experimental laboratory using post-test only control group design. There were seven treatment groups in this study, namely 2,500 ppm, 5,000 ppm, 10,000 ppm, 15,000 ppm, and 20,000 ppm of n-hexane extract of Momordica charantia leaves, a negative control group containing 0.9% NaCl, and a positive control group containing 8,000 ppm albendazole. Ascaris suum is obtained from pig intestines. Ascaris suum was incubated for 24 hours at 37oC. Data analysis was done using the pearson correlation and probit analysis. The extract causes Ascaris suum mortality with LC99 of extract = 23,940 ppm. Ascaris suum mortality with high concentration was strongly correlated (Sig. (2-tailed) 0.971). n-hexane extract from Momordica charantia leaves has the potential to cause Ascaris suum mortality.